Economics as Applied Ethics - Beckerman, Wilfred (Springer, 2017)
This is a substantially revised version of the first edition. Some of the chapters have been largely rewritten, notably the chapters on ‘happiness’, the valuation of life and the problem of equality. In addition, Chapter 1 of the first edition has been scrapped and substantial changes have been made to all the opening chapters in order to bring out more clearly the main theme of this book. This is an attempt to provide a simple method for analysing any problem in economic policy. The method is basically a distinction between what parts of the problem are questions of fact and what parts are questions of value judgement. Consequently, after an initial explanation of the basic concepts involved, the rest of the book comprises a discussion of the way that this distinction crops up in the analysis of applied economic problems. This begins with a general explanation of the role of facts and value judgements in the general theory of welfare economics, and is followed by the application of this distinction to some major contemporary economic problems, such as equality or obligations to other countries or future generations. Thus I make no attempt to provide a general survey of ethics in economics, on which there are already several excellent texts available. Instead I focus on trying to provide a practical key to the analysis of economic policy issues. I believe that this key – namely the separation of questions of fact from questions of value – is one that can also be used profitably to unlock the complexities of non-economic problems as well. But that is another matter. All that I try to do is to bring out into the open the value judgements hidden away in the general theory of welfare economics and in the analysis of many economic policy problems of our time.
Fact and Value in Economic Policy